The effect of eye-hand coordination, kinesthetic perception and anxiety on the results archery scoring of athlete u-12 west jakarta - Aziz Arifin; Ika Novitaria Marani; Mansur Jauhari (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to reveal the direct and indirect effects, as well as the simultaneous effect of exogenous variables on endogenous variables. The sample in this study were 37 archers from all clubs in the West Jakarta area. The research approach used in this study is an associative quantitative approach with test techniques. The data analysis technique uses a path analysis approach (path analysis). The results showed that: 1) there was a direct effect of eye-hand coordination on the archery scores of U-12 archery athletes in West Jakarta amounted to 6.7%, 2) there was a direct influence of kinesthetic perception on the results of archery scoring results for U-12 archery athletes in West Jakarta. is 1.69%, 3) there is a direct and significant effect of anxiety on the archery scores of U-12 archery athletes in West Jakarta, which is 15.8%, 4) there is a direct and significant effect of eye-hand coordination on the anxiety of U-12 archery athletes. West Jakarta by 43.96%, 5) there is a direct and significant effect of kinesthetic perception on the anxiety of West Jakarta U-12 archery athletes by 44.76%, 6) there is an indirect effect of eye-hand coordination through anxiety on archery scoring results are of 27.35%, 7) there is an indirect effect of kinesthetic perception through anxiety on the archery scoring results of 18.9%.